Synergy Between Teachers and Parents in Shaping Students' Responsible Learning Character at MAN 1 Medan: Collaboration Model and Its Challenges - Hasibuan, Rosid Fauzan; Siregar, Nasrun Salim (Journal of Educational Sciences, 2025)
Character education is a crucial aspect of student development to foster responsible and independent generations. The synergy between teachers and parents plays a key role in optimizing the formation of students’ responsible learning character in the madrasah environment. This study aims to examine the synergy between teachers and parents in shaping students' responsible learning character at MAN 1 Medan and to identify the challenges faced in this collaboration. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results indicate that the synergy between teachers and parents is quite well established in a collaborative pattern, where teachers act as academic mentors and character builders at school, while parents provide moral support and supervision of learning at home. This synergy is reflected in active communication through parent-teacher meetings, social media groups, and parental involvement in various school activities. However, this collaboration faces several challenges, such as limited time available for parents, a low understanding of the importance of home education, and differences in socioeconomic backgrounds. These findings emphasize the importance of building strategic partnerships between schools and families in shaping students' responsible learning character sustainably in the madrasah environment.